Analisis Dampak Pendaftaran Tanah Sistematis Lengkap (PTSL) Terhadap Pembangunan Wilayah di Kelurahan Girian Indah Kota Bitung - Rotinsulu , Hendro Novly; Loho, Agnes Estephina; Benu, Noortje Marsellanie (Sam Ratulangi University, 2023)
This study aims to analyze the implementation of the Complete Systematic Land Registration (PTSL) program and the impact of the implementation of the Complete Systematic Land Registration (PTSL) program on the regional economy (access to income) in Girian Indah Village, Bitung City, North Sulawesi. The research sample consisted of 30 respondents who participated in the Complete Systematic Land Registration (PTSL) program. The sample determination was based on data from the Girian Indah urban village office which recorded PTSL certificate recipients who pledged certificates as business capital. Data collection methods used are observation, interview. The research method used is the survey method. The data used is divided into two, namely primary data obtained from respondents who use their certificates in banks while secondary data obtained from agencies related to this research, namely BPN Bitung, literature both reference books and journals. The data was analyzed using quantitative analysis with paired t test data analysis, namely seeing the difference in income before and after the Complete Systematic Land Registration (PTSL) program. The results showed that the implementation of the Complete Systematic Land Registration (PTSL) program had gone well and met the indicators, namely communication, resources, disposition, and bureaucratic structure. In addition, the Complete Systematic Land Registration (PTSL) program has had a positive impact on local revenue in the form of additional income from PPB tax due to the issuance of land certificates but has not had a real effect on community income.